Cross-cultural adaptation: South African Gestational Diabetes Mellitus Knowledge Questionnaire - Lorisha Manas; Tawanda Chivese; Ankia Coetzee; Magda Conradie; Linzette D. Morris (South African Family Practice)
Background: Many serious adverse events associated with gestational diabetes mellitus (GDM) can be mitigated by timely glucose control during pregnancy, achieved through education and lifestyle choices. The aim of this study was to translate and cross-culturally adapt and test the preliminary internal consistency and test-retest reliability of the South African English, Afrikaans and isiXhosa versions of the GDM Knowledge Questionnaire (GDMKQ).